Maḥmūd Shaltūt’s Wasaṭiyyah Approach to Al-Azhar Reform - Md Yusoff, Mohammad Yusri Yubhi; Ushama, Thameem (Advances in Social Sciences Research Journal, 2022)
This article examines Shaltūt’s wasaṭiyyah approach to reform Al-Azhar from his early working days until he was appointed as the Shaykh al-Azhar. In understanding the context of Shaltūt’s reform, this study begins by highlighting Shaltūt’s predecessors, particularly al-Marāghī and al-Ẓawāhirī’s achievements towards reform at Al-Azhar. This study also touches upon ʿAbduh’s pioneering role in generating reforms among Azhari reformists, including Shaltūt and many others before him. These three influential figures are chosen not only for their different reform methods due to their traditionalist and modernist backgrounds but also for their influences and roles in shaping Shaltūt’s approach to reform. Finally, this study explores Shaltūt’s contributions and struggles in presenting his reform ideas against Azhari’s traditionalist opposition scholars. This study is primarily based on textual research; therefore, it is qualitative. To analyse the data, the researcher applies analytical and comparative methods. Consequently, the study concludes that Shaltūt adopted the wasaṭiyyah approach between ʿAbduh, al-Marāghī and al-Ẓawāhirī in reforming Al-Azhar. This wasaṭiyyah approach, not only in administrative but also in curriculum, led to the establishment of the 1961 Al-Azhar Law.